Digitalization Of Legendary Foods To Support Culinary Tourism In Yogyakarta City Region - Rinawati, Wika; Harsana, Minta; Fauziah, Afia (Green Publisher Indonesia, 2023)
This research aims to 1) generate data mapping legendary culinary foods in the city of Yogyakarta, and 2) create a media that serves as a reference for tourists in the city of Yogyakarta. The research uses a descriptive research method to understand the mapping of legendary culinary items and create a digital map application for legendary culinary items. The data analysis employed the test case analysis (Guttman scale) to assess the success of application access and the USE Questionnaire for users. The research was conducted in the Yogyakarta City area through interviews, observations, and documentation. The findings of this research are as follows: 1) The mapping of legendary culinary items in the city of Yogyakarta is differentiated based on the age of the businesses and the types of food sold. The mapping by business age reveals 60 businesses, with those under 25 years accounting for 10% (6 businesses), those between 25-50 years accounting for 30% (18 businesses), and those over 50 years accounting for 60% (36 businesses) of the total. The categorization based on types includes souvenirs, traditional snacks, meatball soup, soto (traditional soup), noodles, gudeg (traditional Javanese jackfruit dish), beverages (traditional and fresh), restaurants, and eateries. 2) The mapping results have led to the creation of a digital mapping application for legendary culinary items. The application, validated by media experts, was found to be easily and smoothly accessible. In user testing, the application received a high level of approval, with 85.8% of respondents strongly agreeing, 13.9% agreeing, and only 0.3% stating that the application was not acceptable. Therefore, it can be concluded that the digital mapping application for legendary culinary items is well-received by users.